1989
DOI: 10.1111/j.1526-4610.1989.hed2907445.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Cranial Electrotherapy in the Treatment of Tension Headache

Abstract: One hundred patients were enrolled in a multicenter double-blind study to evaluate the safety and effectiveness of the Pain Suppressor Unit, a cranial electrotherapy stimulator for the symptomatic treatment of tension headaches. Treatment consisted of extremely low level, high frequency current applied transcranially. Pain scores before and after 20 minute treatments of individual headaches as well as patient and physician global evaluations were the primary efficacy variables. Following use of the active unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…A multicentre double-blind RCT on 100 patients with tension headache reported that TCES signi cantly reduced pain intensity when compared with placebo. 154 RCTs have also found positive effects of TCES on stress-related symptoms in people with closed head injury 155 and in reducing anxiety during routine dental procedures, 156 which may indirectly reduce pain. Recently, Scherder et al 157 reported that TCES produced no improvements in cognition and (affective) behaviour in 18 patients with Alzheimer's disease when compared with placebo.…”
Section: Transcutaneous Cranial Electrical Stimulationmentioning
confidence: 98%
“…A multicentre double-blind RCT on 100 patients with tension headache reported that TCES signi cantly reduced pain intensity when compared with placebo. 154 RCTs have also found positive effects of TCES on stress-related symptoms in people with closed head injury 155 and in reducing anxiety during routine dental procedures, 156 which may indirectly reduce pain. Recently, Scherder et al 157 reported that TCES produced no improvements in cognition and (affective) behaviour in 18 patients with Alzheimer's disease when compared with placebo.…”
Section: Transcutaneous Cranial Electrical Stimulationmentioning
confidence: 98%
“…Solomon et al 53 Lack of diagnostic specificity; IHS criteria were not used for subject enrollment. Cranial electrotherapy is a specialized treatment technique; methodology was not considered relevant by the GDC for the chiropractic care of patients with headache.…”
Section: Appendix Amentioning
confidence: 99%
“…On the other hand, a recent study of TENS found it to be significantly more effective than biofeedback, indepen dently of whether or not it was combined with physiotherapy [124], A modified form of this treatment, which employs high-frequency and low-intensity electric currents, maximum 4 mA ('Pain Suppressor Unit'), appears to be interesting. This technique was tested by So lomon et al [123]. A high or moderate im provement is reported in about 40% of pa tients versus 16% obtained in patients treated with placebo.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Standard TENS uses low-fre quency electric current of about 40-80 mA, applied on the skull. It should be said that it is not held to be completely innocuous [123]; moreover, there is uncertainty as to its effec tiveness [35]. On the other hand, a recent study of TENS found it to be significantly more effective than biofeedback, indepen dently of whether or not it was combined with physiotherapy [124], A modified form of this treatment, which employs high-frequency and low-intensity electric currents, maximum 4 mA ('Pain Suppressor Unit'), appears to be interesting.…”
Section: Other Treatmentsmentioning
confidence: 99%